EMI DYNAMICS: AN EMPIRICAL STUDY ON STUDENTS’ PERSPECTIVES AT TERTIARY LEVEL IN TÜRKİYE - Ekoç Özçelik, Arzu; Kavanoz, Suzan; Yılmaz, Selahattin (Sustainable Multilingualism / Darnioji daugiakalbystė, 2024)
The unprecedented adoption of English-Medium Instruction (EMI) in higher education on a global scale has brought about challenges as well as opportunities for students, which necessitates a careful consideration of factors impacting their perceptions and experiences. Recognizing this critical need, our study attaches significant importance to delve into the attitudes of tertiary-level students towards EMI and aims to evaluate the attitudes and language-related challenges encountered by students in full EMI undergraduate programs. Data were collected from 278 undergraduate students in various full EMI programs at a Turkish public university. Utilizing the culturally and linguistically adapted form of Yeh's (2014) EMI questionnaire, the study focused on students' backgrounds, motivations, and attitudes towards EMI courses, challenges, learning strategies, and beliefs about EMI policies. The findings indicate generally positive attitudes towards EMI. Students perceive EMI as beneficial to their academic and professional development, viewing it as an opportunity to enhance their English proficiency. Nevertheless, challenges arise from coping with specialized terms, heavy learning load, and lecturers’ accents. These results offer valuable insights into the experiences of undergraduate students in full EMI programs at a state university, highlighting both the positive facets and challenges they encounter in settings where English is used as a vehicle for academic growth.